Hyperperfusion and blood-brain barrier disruption beyond the diffusion-restricted infarct 1 day after successful mechanical thrombectomy - Mutke, Matthias Anthony; Potreck, Arne; Möhlenbruch, Markus Alfred; Heiland, Sabine; Mundiyanapurath, Sibu; Pham, Mirko; Bendszus, Martin; Hoffmann, Angelika (American journal of neuroradiology, 2025)
BACKGROUND AND PURPOSE: Patterns of the cerebral microcirculatory response with changes in the BBB and perfusion in patients with stroke and a large vessel occlusion are still unclear. We combined dynamic contrast-enhanced (DCE) permeability and DSC perfusion MRI to detect such patterns beyond the borders of the diffusion-restricted infarct core after successful recanalization. - MATERIALS AND METHODS: Combined DCE permeability and DSC perfusion MRI were performed prospectively in patients within 24 hours after successful mechanical recanalization of acute MCA occlusion. Perfusion alterations were visually assessed on CBF and CBV maps; blood-brain barrier disruptions (BBBD), on Ktrans maps; and they were quantitatively evaluated with an ipsi- to contralateral ratio. Additionally, logistic regression analysis was performed for favorable early clinical outcome (NIHSS ≤2 at discharge). - RESULTS: Thirty-eight patients were included in the study. Subtle hyperperfusion beyond the DWI lesion was present in 13/38 patients (34%) on CBF-maps; and elevated CBV, in 15/38 patients (39%). In these patients, the ratios between ipsi- and contralateral white matter CBF (P = .01) and CBV (P < .01) were elevated compared with patients with normal readings. Subtle, but visually and quantitatively elevated Ktrans values outside the DWI-lesion were observed in 7/38 patients (18%). None of these perfusion alterations were related to clinical outcome. - CONCLUSIONS: Combined DCE permeability and DSC perfusion imaging is feasible in patients 24 hours after successful thrombectomy and reveals subtle hyperperfusion and BBBD occurring frequently beyond the diffusion-restricted infarct core.